Analysis of the Influence of Childhood Fears on the Formation of Adult Stereotypes - Власова, Олена Іванівна; Потонська, О. (Київський національний університет імені Тараса Шевченка, 2021)
The childhood fears and demonstration of their consequences in adult life is an important topic of psychology and psychiatry. The analysis of theoretical studies, allows to reveal more deeply consequences of formation and functioning of stereotypes in consciousness and behavior of people. The phenomenon of stereotype from a psychological and psychophysiological point of view is considered in the article. The psychological understanding of the concepts of stereotype and fear is provided on the basis of the analysis and generalization of related materials. The different interpretations of the stereotype have been found to reflect the different aspects of the same phenomenon: physiological basis, social and psychological conditioning, behavioral and verbal realization. The determinants (external and internal) of the appearance of the stereotype of person's behavior have been determined and the relations between the individual determinants have been revealed. In particular, the influence of childhood fears on the formation of adult stereotypes was revealed. The main goal is to systematize and generalize the scientific concepts regarding the influence of childhood fears on the formation of adult stereotypes. The main research methods: Analysis and synthesis of information on professional sources. The problem statement. The one of the most important characteristics of stereotypes is their diversity, which makes them function in all spheres of society in different modifications. It is first necessary to develop its generalized, detailed methodological typology based on various scientific classifications in order to study the problem of the formation of stereotypes of human behaviour under the influence of childhood fears. The various fears, both normal and pathological, influence the adult behaviour. The normal fears of a child are always reactions to real dangers, the consequences of which the child assesses adequately, without overstating or minimizing the consequences. The pathological fears are considered to hinder the development of children, their communication with their peers and their social inclusion, and cause various mental disorders. The reaction of the child to such abnormalities is disobedience, reduced academic performance, behavioural disorders and communication with peers and parents. The greater influence of childhood fears when they are laid down for the future, when adults take certain steps under the influence of stereotypes created by their own experience, in which the fears of different levels of intensity and importance were significant. The stereotypes that define the character of the person and his behavior in adulthood go through a long period of formation. The stereotype takes effect even before the mind, the intelligence, puts a specific imprint on the data that the human senses perceive even before the data reaches the mind. At the same time, certain stimuli, especially those inherited by an adult from his or her childhood, activate a certain part of the stereotype system. Thus, the direct impression and a certain evaluation, which has been formed earlier, appear in consciousness simultaneously. The fears inherited by the adult from the period of childhood can carry out a number of characteristic reconstructions in consciousness, which are reflected in individual links of the system, in the entire system or, finally, in the entire above nervous activity.

Розглянуто дитячі страхи та прояв їх наслідків у дорослому житті людини, що є важливою темою психології та психіатрії. Проведено теоретичні дослідження, які дали змогу глибше розкрити наслідки формування та функціонування стереотипів у свідомості і поведінці людей. Систематизовано й узагальненено наукові концепцїй стосовно впливу дитячих страхів на формування стереотипів дорослої людини. Як основні методи дослідження використано аналіз та узагальнення інформації з фахових джерел. Всебічно розглянуто явище стереотипу з психологічного та психофізологічного поглядів. На основі аналізу та узагальнення дотичних матеріалів представлено психологічне розуміння понять "стереотип" і "страх". З'ясовано, що різні трактування стереотипу відображають різні сторони одного явища: фізіологічний базис, соціальну та психологічну обумовленість, поведінкову і вербальну реалізацію такого психологічного механізму. Визначено детермінанти (зовнішні та внутрішні) прояву стереотипу поведінки людини і розкрито відношення між окремими детермінантами та становленням стереотипів, у тому числі виявлено впливи дитячих страхів на формування стереотипів дорослої людини. Емпіричне дослідження підтвердило, що особи з вираженими дитячими страхами демонструють достовірно більшу схильність до стереотипності, що проявляється в інтоленрантності до невизначеності (як стосовно міжособистісних стосунків, так і світу взагалі), сприйнятті навколишнього світу та життєвих подій як потенційно небезпечних, стереотипних емоційних реакціях тривоги, схильності до ірраціональних когнітивних установок та хибних переконань (насамперед низької фрустраційної толерантності). Все це є джерелом неадаптивних поведінкових реакцій, що призводить до формування співзалежності, особистісних розладів та психологічного неблагополуччя.
Аналіз впливу дитячих страхів на формування стереотипів дорослої людини
Keywords: anticision; determinants; intolerance; rigidity; stereotype; fear; антиципація; детермінація; інтолерантність; ригідність; стереотип; страх